1990
DOI: 10.1111/j.1532-5415.1990.tb01425.x
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of an Influenza‐Like Illness in a Nursing Home

Abstract: As part of an ongoing infection surveillance program, data were collected on an outbreak of respiratory illness affecting 29% of residents in a 231-bed long-term care facility. Viral titers could be collected on 60% of the ill residents and respiratory syncytial virus (RSV) was established in 14 of the symptomatic patients and was thought to be the probable cause of the outbreak. Compared with previously reported long-term institutional outbreaks of RSV, there were significantly fewer cases of pneumonia (5% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…7 Among patients in hospitals and long-term care facilities, RSV infection has resulted in exacerbations of chronic lung disease in 5 to 50 percent of cases and a mortality rate reaching 20 percent. [62][63][64] The importance of RSV infection as a cause of hospitalization in previously healthy adults has been recognized more recently. Of 1195 adults admitted to a hospital with community-acquired pneumonia in Ohio, 4.4 percent had RSV infection.…”
Section: Reinfections In Previously Healthy Personsmentioning
confidence: 99%
“…7 Among patients in hospitals and long-term care facilities, RSV infection has resulted in exacerbations of chronic lung disease in 5 to 50 percent of cases and a mortality rate reaching 20 percent. [62][63][64] The importance of RSV infection as a cause of hospitalization in previously healthy adults has been recognized more recently. Of 1195 adults admitted to a hospital with community-acquired pneumonia in Ohio, 4.4 percent had RSV infection.…”
Section: Reinfections In Previously Healthy Personsmentioning
confidence: 99%
“…Interestingly, natural RSV infection does not confer lifetime immunity [10] and therefore individuals are repeatedly infected throughout life. Healthy adults develop cold-or flu-like symptoms whereas the elderly [11][12][13][14] and immunocompromised individuals [15,16] have increased risk of severe respiratory illness. Moreover, a recent study has indicated that RSV disease burden in the elderly is similar to that of nonpandemic influenza A [17].…”
Section: Introductionmentioning
confidence: 99%
“…RSV infections typically cause mild illness, however severe disease can occur and is often associated with symptoms such as bronchiolitis and wheezing [6]. Populations at greatest risk to develop severe disease after RSV infection include premature infants [7], persons with congenital heart disease [8][9][10], immunocompromised individuals [11,12], and the elderly [11,13,14]. Clinical studies have indicated that children that are hospitalized due to RSV-induced disease exhibit an increased incidence of asthma later in life as compared to children that experience a mild or asymptomatic RSV infection (recently reviewed in [15]).…”
Section: Introductionmentioning
confidence: 99%